2015
DOI: 10.1002/hep.27709
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin plus albumin versus midodrine and octreotide plus albumin in the treatment of hepatorenal syndrome: A randomized trial

Abstract: Hepatorenal syndrome (HRS), a serious complication of cirrhosis, is associated with high mortality without treatment. Terlipressin with albumin is effective in the reversal of HRS. Where terlipressin is not available, as in the United States, midodrine and octreotide with albumin are used as an alternative treatment of HRS. The aim was to compare the effectiveness of terlipressin plus albumin versus midodrine and octreotide plus albumin in the treatment of HRS in a randomized controlled trial. Twenty‐seven pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
225
1
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(247 citation statements)
references
References 29 publications
11
225
1
10
Order By: Relevance
“…Furthermore, a recent study indicated that the efficacy of a midodrine plus octreotide regimen might not be as significant as previous studies suggested (17). In 2015, a randomised controlled trial of 49 patients comparing terlipressin with octreotide/midodrine illustrated a significantly higher rate of improvement in renal function with terlipressin (≥50% serum creatinine decrease, 70.4% vs. 28.6%, P = 0.01), although there was no significant difference in survival between the two groups (18). Terlipressin is a bridging option, despite its high cost, to liver transplantation in patients who are transplant candidates as it may improve both renal function and short-term survival for patients awaiting a liver transplant.…”
Section: Vasoconstrictor Therapymentioning
confidence: 95%
“…Furthermore, a recent study indicated that the efficacy of a midodrine plus octreotide regimen might not be as significant as previous studies suggested (17). In 2015, a randomised controlled trial of 49 patients comparing terlipressin with octreotide/midodrine illustrated a significantly higher rate of improvement in renal function with terlipressin (≥50% serum creatinine decrease, 70.4% vs. 28.6%, P = 0.01), although there was no significant difference in survival between the two groups (18). Terlipressin is a bridging option, despite its high cost, to liver transplantation in patients who are transplant candidates as it may improve both renal function and short-term survival for patients awaiting a liver transplant.…”
Section: Vasoconstrictor Therapymentioning
confidence: 95%
“…40 However, terlipressin was superior to midodrine and octreotide in a randomized controlled trial. 41 In patients who require IV vasopressor support, use of norepinephrine is preferred in patients with cirrhosis because it has been shown to improve renal outcomes in patients with HRS. Notably, terlipressin was compared to norepinephrine for the treatment of HRS, and no difference was found between the interventions.…”
Section: Renal Failurementioning
confidence: 99%
“…We appreciate the interest of Vasudevan et al in our article recently published in HEPATOLOGY (1) on the use of terlipressin by continuous infusion, a schedule we introduced in 2006 in the treatment of hepatorenal syndrome (HRS). (2) We read with interest their experience with the outpatient continuous infusion of terlipressin in patients with HRS on the liver transplant (LT) waiting list.…”
Section: Replymentioning
confidence: 99%